2011
DOI: 10.1289/ehp.1002705
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons–Aromatic DNA Adducts in Cord Blood and Behavior Scores in New York City Children

Abstract: Background: Airborne polycyclic aromatic hydrocarbons (PAH) are widespread urban pollutants that can bind to DNA to form PAH–DNA adducts. Prenatal PAH exposure measured by personal monitoring has been linked to cognitive deficits in childhood in a prospective study conducted by the Columbia Center for Children’s Environmental Health.Objectives: We measured PAH–DNA and other bulky aromatic adducts in umbilical cord white blood cells using the 32P-postlabeling assay to determine the association between this mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(85 citation statements)
references
References 56 publications
2
81
2
Order By: Relevance
“…Levels of PAH-DNA adducts in cord blood have been found to be associated with higher symptom scores of anxiety and depression measured at 4.8 years (Perera et al, 2011). In the same cohort, prenatal exposure to benzo[a]pyrene measured from maternal personal air monitoring (at a median level of 2.27 ng/m 3 ), and also cord blood adduct levels, were associated with these effects, as well as attention problems at age 6-7 years .…”
Section: Rationalementioning
confidence: 99%
“…Levels of PAH-DNA adducts in cord blood have been found to be associated with higher symptom scores of anxiety and depression measured at 4.8 years (Perera et al, 2011). In the same cohort, prenatal exposure to benzo[a]pyrene measured from maternal personal air monitoring (at a median level of 2.27 ng/m 3 ), and also cord blood adduct levels, were associated with these effects, as well as attention problems at age 6-7 years .…”
Section: Rationalementioning
confidence: 99%
“…A new hypothesis suggests that a greater susceptibility to air pollutants may be linked with genomic polymorphism [29] and reduced levels of DNA methylation associated with oxidative stress, by altering the expression of genes involved in the methylation process. In the context of potential epigenetic effects of air pollutants, we have to mention observations made recently by Perera et al [30] in the New York City cohort study on fetal growth and healthy development of children. In the latter study, prenatal exposure It is worth mentioning that the observed dose-dependent relationship without threshold was seen between eCO and fetal exposure to PM 2.5 and that the significant portion of the exhaled CO could be attributed to prenatal PM 2.5 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…PAHs have been shown to be neurodevelopmental toxicants in experimental studies [19][20][21]. There are 8 human epidemiological studies which have examined an association between exposure to PAHs and children's development [22][23][24][25][26][27], one study has investigated how polymorphism in PAH metabolic genes affects child cognitive development [28], and another one has assessed the combined exposure to environmental tobacco smoke (ETS) and PAH-DNA adducts after the World Trade Center catastrophe and its impact on child development [29] (Table 4).…”
Section: Exposure To Pahs and Children's Neurodevelopmentmentioning
confidence: 99%
“…High PAH levels (above 17.96 ng/m 3 ) were inversely associated with fullscale IQ (p = 0.007) and verbal IQ (p = 0.003) scores [23]. The same cohort was followed to 7-8 years of age [24], adducts were measured in umbilical cord blood. Higher cord PAH-DNA and other bulky aromatic adducts were associated with higher symptom scores of anxious/depressed at 4.8 years and attention problems at 4.8 and 7 years, in children born to nonsmoking women, the women's smoking status was based on cotinine level in cord blood [24].…”
Section: Exposure To Bfrs and Children's Neurodevelopmentmentioning
confidence: 99%
See 1 more Smart Citation